Plasma microparticles from patients with systemic lupus erythematosus modulate the content of miRNAs in U937 cells (2021)
ABSTRACT: In systemic lupus erythematosus (SLE), the clearance of apoptotic cells and microparticles (MPs) is reduced. Some MPs contain molecules that can modulate immune responses. This study aimed to evaluate the presence of miR-126 and miR-146a in plasma MPs of patients with SLE (SLE MPs) and analyse the ability of MPs to modulate some events in the promonocytic U937 cell line. Circulating MPs were isolated from plasma samples of healthy controls (HCs), patients with SLE and other autoimmune diseases (OAD). MPs were analysed for size and cell origin by flow cytometry and content of miR-126 and miR-146a by RT-qPCR. MPs were then added to U937 cell cultures to evaluate changes in cell phenotype, cytokine expression, content of miR-126 and miR-146a, and levels of IRF5. Patients with active SLE (aSLE) showed an increase in concentration of plasma MPs that positively correlated with the SLEDAI (SLE Disease Activity Index) score. CD14+ MPs were significantly more abundant in patients with SLE than HCs. SLE MPs contained decreased levels of miR-146a, but the miR-126 content in aSLE MPs was increased. The miR-126 content in SLE MPs correlated positively with the SLEDAI score. The treatment of U937 cells with MPs from HCs and patients induced reduced expression of HLA-DR, CD18 and CD119, increased frequency of IL-6+ and TNF-α+ cells, accumulation of IL-8 in culture supernatants, increased miR-126 levels and decreased miR-146a content, but no change in the expression of IRF5. These findings suggest that plasma MPs, especially SLE MPs, could modulate some biological events in U937 cells.